Neutrosophic Fuzzy Soft Game - Selvakumari, K; Lavanya, S (International Journal of Engineering and Technology, 2018)
The Soft set theory, originally proposed by Molodtsov, can be used as a general mathematical tool for dealing with uncertainity.This paper is devoted to the discussions of Neutrosophic fuzzy soft set. A new game modelis proposed and called Neutrosophicfuzzy soft game since it is based on Neutrosophic fuzzy soft set theory. We concentrate on discussing a class of two person zero-sum games with Neutrosophic fuzzy soft payoffs.The proposed scheme is illustrated by an example regarding the pure strategy problem.Â Â